Abundance of metalloprotease FtsH12 modulates chloroplast development in Arabidopsis thaliana. (20th November 2020) - Mielke, Kati; Wagner, Raik; Mishra, Laxmi S; Demir, Fatih; Perrar, Andreas; Huesgen, Pitter F; Funk, Christiane
Abstract: The ATP-dependent metalloprotease FtsH12 (filamentation temperature sensitive protein H 12) has been suggested to participate in a heteromeric motor complex, driving protein translocation into the chloroplast. FtsH12 was immuno-detected in proplastids, seedlings, leaves, and roots. Expression of Myc-tagged FtsH12 under its native promotor allowed identification of FtsHi1, 2, 4, and 5, and plastidic NAD-malate dehydrogenase, five of the six interaction partners in the suggested import motor complex. Arabidopsis thaliana mutant seedlings with reduced FTSH12 abundance exhibited pale cotyledons and small, deformed chloroplasts with altered thylakoid structure. Mature plants retained these chloroplast defects, resulting in slightly variegated leaves and lower chlorophyll content. Label-free proteomics revealed strong changes in the proteome composition of FTSH12 knock-down seedlings, reflecting impaired plastid development. The composition of the translocon on the inner chloroplast membrane (TIC) protein import complex was altered, with coordinated reduction of the FtsH12-FtsHi complex subunits and accumulation of the 1 MDa TIC complex subunits TIC56, TIC214 and TIC22-III. FTSH12 overexpressor lines showed no obvious phenotype, but still displayed distinct differences in their proteome. N-terminome analyses further demonstrated normal proteolytic maturation of plastid-imported proteins irrespective of FTSH12 abundance. Together, our data suggest that FtsH12 has highest impact during seedling development; its abundance alters the plastid import machinery and impairs chloroplast development. Abstract : Modulation of metalloprotease FtsH12 abundance in Arabidopsis results in altered composition of the plastid import machinery, which in turn affects the development of functional chloroplasts.